2016
DOI: 10.3168/jds.2015-10732
|View full text |Cite
|
Sign up to set email alerts
|

Virulence profile and genetic variability of Staphylococcus aureus isolated from artisanal cheese

Abstract: The objectives of this study were to characterize Staphylococcus aureus isolated from artisanal and industrialized Minas frescal cheeses, to determine their antimicrobial susceptibility profile as well as the genetic similarity among the isolates. The isolates were also tested for staphylococcal enterotoxin genes and other virulence factors. Fifty-six artisanal raw milk cheeses sold at street fairs and 10 industrialized cheeses commercialized in supermarkets of Goiânia, Goiás, were analyzed. Staphylococcus aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
13
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 43 publications
(51 reference statements)
6
13
1
4
Order By: Relevance
“…In the present survey, tss , eta , etb , and pvl genes were not found in the MRSA and methicillin‐susceptible S. aureus strains. Our findings are consistent with the results of Ferreira et al () and Song et al () which documented the absence of these genes in MRSA strains isolated from cheese and milk samples, respectively. A similar observation was made in the study conducted in Turkey of Sudagidan and Aydin () who did not detect eta , etb , and tst genes in food isolates of methicillin‐susceptible S. aureus .…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In the present survey, tss , eta , etb , and pvl genes were not found in the MRSA and methicillin‐susceptible S. aureus strains. Our findings are consistent with the results of Ferreira et al () and Song et al () which documented the absence of these genes in MRSA strains isolated from cheese and milk samples, respectively. A similar observation was made in the study conducted in Turkey of Sudagidan and Aydin () who did not detect eta , etb , and tst genes in food isolates of methicillin‐susceptible S. aureus .…”
Section: Discussionsupporting
confidence: 94%
“…The same result was found by Ektik et al (), and similar results were published by Papadopoulos et al () with 99.3% resistance and by Can et al () with 95% resistance. Consistent with our data, several studies performed in different countries also reported resistance to tetracycline (Can & Çelik, ; Ferreira et al, ; Oniciuc et al, ; Pamuk et al, ; Papadopoulos et al, ; Traversa et al, ), clindamycin (Can & Çelik, ; Pamuk et al, ; Traversa et al, ), and chloramphenicol (Pamuk et al, ; Papadopoulos et al, ). In addition to antibiotics tested in the present study, resistance to erythromycin (Can & Çelik, ; Pamuk et al, ; Traversa et al, ), ampicillin (Can & Çelik, ; Ektik et al, ), and ciprofloxacin (Oniciuc et al, ; Papadopoulos et al, ) has been reported in milk and dairy isolates of MRSA.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations